Sarampión y sus complicaciones - Durán Álvarez, Sandalio; Cuán Leal, María Victoria; Izquierdo Gener, Juan; Espinosa del Risco, Eduardo; Muñoz Rodríguez, Rafael (Revista Cubana de Pediatría, 2023)
Señala las complicaciones y el número de casos ingresados en el primer cuatrimestre de 1969.